Inferior Vena Cava Thrombosis: Taking a Second Look at the Inferior Vena Cava in Trauma Patients - Sara Hussain; Firas Al Najjar (Dubai Medical Journal, 2020)
We present the case of a patient who fell from a 3-m height. He was bought to the emergency department and immediate resuscitative measures were taken. His GCS on presentation was 15, and the airway was patent and maintainable. Breathing was equal bilaterally, the blood pressure and capillary refill were established to be normal, and a bedside E-FAST scan was negative. He was found to have a dislocated left knee, with sensorineural loss distal to the injury. After the dislocation was reduced, a whole-body CT scan was performed and revealed an incidental finding of thrombus in the inferior vena cava (IVC). A thrombus in the IVC by itself is an uncommon complication among trauma patients, but among the cases noted in literature, most patients with an IVC thrombus had a slightly delayed presentation and it was usually discovered a few days after admission. Management of the thrombus depends on the stability of the patient’s presentation. When feasible, operative or otherwise invasive procedures can be delayed, allowing for the medical management of the thrombus. IVC filters may also be used, but their use may be limited due to anatomical restrictions, as in our case.